Digital resources for transfusion education - Maria-Angustias; Elena Fernández-Guerrero; Francisco-Javier A; Cristóbal Avivar-Oyonarte (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Regular training in the blood transfusion process is crucial for transfusion safety. Hospital transfusion committees have an obligation to provide this education to hospital employees through training activities. E-learning is positioning itself as a valid alternative to physical-presence courses. MATERIALS AND METHODS: We describe a training course on blood transfusion to members of our hospital who are involved in the transfusion process, including technicians, nurses, and doctors. The course uses Moodle as the e-learning platform; it is evaluated using a satisfaction survey along with a knowledge-transfer and impact survey a year after taking the course. RESULTS: From 2015 to 2018, seven editions of the online transfusion course were developed. Six hundred and eighty students enrolled; of these, 124 did not take the final examination (18.2%); 60 never began the course (8.8%). Of the 556 students who completed the course, 546 passed (98.2%). The average score from the initial self-assessment was 7.3 while the average score from the final self-assessment was 9.2; the mean improvement was 1.9 (out of 10). The level of general course satisfaction was 9.27 (an average out of 10). More than 90% of the students stated that they were able to apply the acquired knowledge in the workplace after a year. CONCLUSIONS: E-learning has demonstrated itself as an affordable solution that could help in the training of all staff involved in the transfusion process at our hospital, with the advantage that it includes general knowledge and particular skills in local transfusion medical practice.